(untitled) (Academia Journal of Medicine, 2026)
Supernumerary teeth are developmental anomalies characterized by the presence of teeth in excess of the normal dentition, occurring in both primary and permanent dentitions. They are most commonly observed in the maxillary anterior region as mesiodens and may lead to various complications such as delayed eruption, crowding, midline diastema, and impaction of adjacent teeth. The etiology is considered multifactorial, with the dental lamina hyperactivity theory being the most widely accepted, along with genetic and syndromic associations. Advances in diagnostic techniques, particularly cone-beam computed tomography, have significantly improved the localization and assessment of these teeth, facilitating precise treatment planning. Management strategies range from periodic observation to surgical removal, often followed by orthodontic intervention, with the timing of extraction remaining a subject of ongoing debate. This review aims to provide a comprehensive and updated overview of the etiology, classification, clinical features, diagnosis, and management of supernumerary teeth, with emphasis on recent advances and their clinical implications